A facile and green approach to prepare carbon dots with pH-dependent fluorescence for patterning and bioimaging. Issue 66 (13th November 2018) - Guo, Xin; Zhu, Yufu; Zhou, Lei; Zhang, Linna; You, Yucai; Zhang, Hongliang; Hao, Jiajia
Abstract : Carbon dots prepared with the adoption of ubiquitous natural fruit juices as precursors have good applications in pH sensing, patterning and bioimaging. Abstract : As the new representative in the carbonaceous family, carbon dots (CDs) have gained remarkable research interests over the past decade. Herein, we report the facile preparation and thorough performance comparison of three types of carbon dots with the adoption of ubiquitous natural fruit juice as precursors and demonstrate their application in pH sensing, patterning and bioimaging. All the yielded CDs show interesting optical properties including evident single- or two-photon absorption and excitation-dependent photoluminescence along with the high fluorescent yield. A detailed study on the physical properties by EPR and Stokes shift analysis and structural composition analysis by XPS and Raman spectroscopy suggest that the fluorescence of CDs originates from the electron–hole recombination via the defect state. In addition, through the regulation of non-radiative recombination rate of CDs, all the obtained CDs could be applied as fluorescent sensing platforms toward the sensitive detection of the solution pH changes by the indication of CDs' fluorescent yield and lifetime variation. Moreover, it was also proven that the resulting CDs could be employed as fluorescent inks for printing patterns in anti-counterfeit applications and as fluorescent probes for bioimaging of osteoblasts.